Autism spectrum disorder and schizophrenia: a phenomenological comparison - Schnitzler, Tim; Fuchs, Thomas (Frontiers in psychiatry, 2025)
A mental illness can lead to a distortion in a person’s capacity to engage with the world and other people in a variety of ways. This is particularly relevant to schizophrenia and autism spectrum disorder (ASD), which are not only historically linked, but also overlap clinically in several respects. From a phenomenological point of view, the differences or similarities between both disorders have not yet been sufficiently investigated. Schizophrenic autism can be characterized as a disorder of three interconnected dimensions, namely the self, intersubjectivity and the self’s relationship with the life-world. The present work therefore investigates differences in these three dimensions between the two disorders. One key difference is that the self-world relationship in schizophrenia can be described as unstable or fragmented, whereas in ASD it is considered stable. Finally, possible differences in the experience of delusions are discussed as a change in the self’s relationship with the world.